2003
DOI: 10.1046/j.1365-2303.2003.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of fine needle aspiration cytology of the breast – comparison of Auto Cyto Fix and conventional smears

Abstract: In Japan, there are some problems with fine needle aspiration (FNA) cytology of the breast, such as insufficient smeared cells, air-drying artefact and excessive erythrocytes. Liquid-based cytology has been found to solve these problems. Equipment for such preparations has been developed, but can be expensive to purchase and operate. We developed Auto Cyto Fix 1000 (ACF), which is inexpensive and automatically smears and fixes cells. The purpose of this study was to compare the various cytological features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[54][55][56][57][58] Recent studies have suggested that problems with FNA cytology of the breast, such as insufficient cells or air-drying artifact, are solved by liquid-based technology. [55][56][57] FNA of ovarian tumors might also benefit from this new method.…”
Section: Ancillary Techniques That Increase the Diagnostic Accuracy Omentioning
confidence: 99%
“…[54][55][56][57][58] Recent studies have suggested that problems with FNA cytology of the breast, such as insufficient cells or air-drying artifact, are solved by liquid-based technology. [55][56][57] FNA of ovarian tumors might also benefit from this new method.…”
Section: Ancillary Techniques That Increase the Diagnostic Accuracy Omentioning
confidence: 99%
“…Nucleoli and subtle nuclear membrane irregularities may appear more prominent. Despite these differences in cellular features, diagnostic accuracy is not significantly different between direct smears and liquid-based collection with thin-layer preparation, once one becomes familiar with these differences [7][8][9][10][11].…”
Section: General Diagnostic Criteria Of Malignancymentioning
confidence: 99%
“…Key features include increased cellularity, the presence of single epithelial cells, angular epithelial clusters, and mild to moderate atypia (Figs. [10][11][12]. Dawson and colleagues [31] emphasize that these features often are not the predominate component on the smears.…”
Section: Tubular Carcinomamentioning
confidence: 99%
“…Using the Auto Cyto Fix 1000 ® (ACF, Chiba, Japan) method, Yamashita et al 8 found that a rather inexpensive method of LBC yielded results similar to those of CSC and stated that the problems of low cellularity, air drying and blood in the background could be alleviated using their LBC method.…”
Section: Introductionmentioning
confidence: 99%